A Study of Exploitation of Minerals from Ocean Floor and Related Environmental Issues: Exploring the Potential of Solid Minerals from the Ocean Floor (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Modern society is in growing need for food, energy, water and minerals. Economic growth and increase in world population are driving demand to the very limits of what the earth can provide for us. People’s basic needs have a marked effect on every level of the world’s supply chains. The increasing wealth of emerging economies has evolved into new standards of living, which demand evermore from our planet’s land, rivers and forests. We must have an open discussion about our individual roles in the sustainability of our societies. To tackle our short-term needs, we must look at all opportunities, on land as well as offshore. However, addressing the long-term problems would require a broad view of technology, human behaviour and innovation. Consumer’s attitudes and behaviours in selecting products and facilities also needs guidance, influenced by the more healthy, renewable and recyclable solutions. The seabed holds vast and diverse resources capable of sustaining human demands for centuries ahead. Key among these resources is solid minerals, biogenic and energy resources. Here in this research paper we are going to confine our study to solid minerals only.